2012
DOI: 10.1007/s00122-012-1839-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in European Pisum germplasm collections

Abstract: The distinctness of, and overlap between, pea genotypes held in several Pisum germplasm collections has been used to determine their relatedness and to test previous ideas about the genetic diversity of Pisum. Our characterisation of genetic diversity among 4,538 Pisum accessions held in 7 European Genebanks has identified sources of novel genetic variation, and both reinforces and refines previous interpretations of the overall structure of genetic diversity in Pisum. Molecular marker analysis was based upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
39
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 28 publications
8
39
0
1
Order By: Relevance
“…This collection of 372 accessions was gathered in order to represent a wide range of phenotypic and passport data diversity. We confirmed (i) that the pea germplasm is structured according to major passport classes as defined by the use type, the population type, and the sowing type and (ii) that the range of genetic variability present in the Pisum sativum germplasm is high, as already pointed out by other authors [4,5,8,9,53]. However, this passport information may be misleading in some cases: the fodder and winter-sowing types are ancestral characteristics present in wild germplasm but can correspond in the collection to contrasted levels of winter tolerance and to different growth habits.…”
Section: Discussionsupporting
confidence: 88%
“…This collection of 372 accessions was gathered in order to represent a wide range of phenotypic and passport data diversity. We confirmed (i) that the pea germplasm is structured according to major passport classes as defined by the use type, the population type, and the sowing type and (ii) that the range of genetic variability present in the Pisum sativum germplasm is high, as already pointed out by other authors [4,5,8,9,53]. However, this passport information may be misleading in some cases: the fodder and winter-sowing types are ancestral characteristics present in wild germplasm but can correspond in the collection to contrasted levels of winter tolerance and to different growth habits.…”
Section: Discussionsupporting
confidence: 88%
“…In a previous study by Jing et al [35], 45 retrotransposon-based insertion polymorphism (RBIP) markers were used to analyze genetic diversity among 3020 pea accessions. They expanded their analysis by including 1518 additional germplasm samples [36]. The genetic diversity analysis among 4538 accessions presented an overall structure of genetic diversity including novel genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Using a limited number of genetic markers, we show that extant Swedish field pea accessions constitute genetically distinct populations, with in many cases clear geographic clustering. Although crop species have spread across the world as recently as in the past 10 000 years, geographical structure has been observed on a continental scale in pea (Jing et al, 2010(Jing et al, , 2012 as well as in other species such as barley (Malysheva-Otto et al, 2006;Jones et al, 2011), maize (van Heerwaarden et al, (2011) and einkorn wheat (Oliveira et al, 2011). On a national scale, reports on geographical structure among pea landraces are rare.…”
Section: Discussionmentioning
confidence: 99%
“…global genetic resources have recently been studied with DNA markers (Baranger et al, 2004;Zong et al, 2009;Jing et al, 2010Jing et al, , 2012. These studies showed that the Pisum germplasm is structured into clades corresponding to taxonomic subdivisions, phenotypic traits and/or different end-use and geographical origin.…”
Section: Introductionmentioning
confidence: 99%